Ethnomedicinal Resources of a Newar Community in Gorkha, Nepal - Bista Adhikari, Sita; Karki, Subash; Chhetri, Parveen K.; Bista, Raju (Our Nature, 2024)
Ethnobiology offers valuable insights into medicinal plants and animals, and their sustainable domestication and management. We explored the traditional medico-ethnobiological knowledge within a Newar community in Gorkha. We collected primary data through interviews, observations, and identified 49 plant and 11 animal species being used for treating ailments locally. Indigenous knowledge transmission mainly involved elders, healers, and parents. We also observed potentially eroding traditional knowledge among the younger generation. School and teachers had limited influence in passing on this knowledge. Preserving this wisdom requires community-focused traditional knowledge transfer mechanisms to integrate local wisdom into conservation and management efforts.